PENGARUH GLISEROL PADA MEDIA TRYPTIC SOY BROTH (TSB) TERHADAP VIABILITAS BAKTERI Aeromonas hydrophila - Jarod Setiaji; T Iskandar Johan; Meliya Widantari (UIR Press, 2015)
The effect of glycerol at the TSB media on Aeromonas hydrophila bacteria viability was studied. The purpose of this study was to obtain the best glyserol concentration in TSB as storage media for Aeromonas hydrophila bacteria. The completely randomized design with one factor was used for four treatments and three replications, i.e., TSB media added glycerol 10%, 15%, 20% and 25%. The stage of this research included media preparation, preliminary test, glycerol preparation, inoculation on kryotube, and test bacteria inspection. The test results showed the highest bacteria growth capacity was found on bacteria stored in TSB that was added with glycerol under concentration of 15%, namely 5.77 x 107 CFU/ml and the lowest one in TSB that was added gluserol 25%, experiencing total death on 56th day. The largest percentage of bacteria viability during storage was obtained on 15% glycerol increment, accounting for 0.01015%, and the lowest one was found on 115% glyserol increment, namely 0%. The aeromonas hydrophila bacteria storage with using glycerol concentration for 10%, 15%, 20% and 25% on temperature -20o C during 56 days did not cause to be occured mutation and change the bacteria charactristics. Percentage of suitable bacteria on mother T (0) was 100%.